Axiological and Methodological Assumptions of the Study of the Fall of the First Polish Republic in the Historical Works by Celina Bobińska - Pasisz, Piotr (Respectus Philologicus, 2019)
[full article, abstract in English; abstracts in English and Polish] The article presents an analysis of the fall of the First Polish Republic in selected works of the PRL historian Celina Bobińska. The issue scope follows the field of the history of historiography which in a narrow sense is the history of historical science. Such research is part of using the words of Andrzej Feliks Grabski, so-called “The subjective history of historiography”. In addition to the intellectual biography of the historian, his work is analysed in the context of changes taking place in the paradigms of practising historical research. I focus on the theoretical and methodological assumptions and the assessments resulting from the adoption of a specific, historically and culturally oriented axiology. The main research questions I ask myself are: What theoretical and methodological assumptions accompanied Celina Bobińska during the examination of the question of the collapse of the Polish state and how the axiology accepted by it conditioned the assessment of this event. The source database – selected monographs by Bobińska from 1949–1956 as the most representative of her work during this period.